비스페놀 A (Bisphenol-A)로 유도된 지방세포 분화에 미치는 갓 추출물의 항오비소겐 효과 - 이세정; 나윤주; 최선일; 한웅호; 문효; 이윤환; 김현덕; 김윤정; 이옥환; Lee, Se-jeong; Na, Uoon-Joo; Choi, Sun-Il; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2021)
The purpose of the study was to investigate the content of sinigrin, an index component, in Brassica juncea extract and to evaluate the differentiation of lipocytes, inhibition of production of reactive oxygen species (ROS) and reduction of protein production by lipogenic factors (PPARγ, C/EBPα, aP2) in the processing of Brassica juncea extract and sinigrin in 3T3-L1 preadipocytes which induces Bisphenol A (BPA), an endocrine disrupting environmental hormone. From the investigation, the content of sinigrin in Brassica juncea extract, measured by HPLC, is found to be 21.27±0.2 mg/g. The XTT assay result on BPA-derived 3T3-L1 adipocytes shows there is no cytotoxicity found from 180 µM of sinigrin and 300 ㎍/mL of Brassica juncea extract. Moreover, both intracellular lipid accumulation and ROS production during differentiation of lipocyte are significantly reduced in cells processed with Brassica juncea extract and sinigrin. Lastly, it was also found that the production of transcription factors of lipocyte differentiation, PPARγ, C/EBPα and aP2, were found to be suppressed by the application of Brassica juncea extract and sinigrin. Such results reveals that Brassica juncea is effective in not only suppressing lipid accumulation in the environmental hormone bisphenol A-derived lipocyte, but also in reducing the ROS. The sinigrin-containing Brassica juncea is highly expected to be used in natural functional supplements that prevents the lipid metabolism disorders caused by BPA. There are necessities for additional clinical research and follow-up studies on the in vivo model to verify the relevant mechanisms. 본 연구는 십자화과 채소인 갓(Brassica juncea) 추출물을 이용하여 지표성분인 sinigrin의 함량을 분석하고, 내분비계 교란물질 환경호르몬인 비스페놀 A (BPA)로 분화를 유도한 3T3-L1 전구지방세포에서 갓 추출물과 sinigrin 처리에 대한 지방세포 분화 및 활성산소종(ROS) 생성 억제, 지방 생성 전사인자(PPARγ, C/EBPα, aP2)의 단백질 발현 감소 효능을 평가하였다. 연구 결과에 따르면 HPLC를 이용하여 측정한 갓 추출물 중 sinigrin의 함량은 21.27±0.2 mg/g 인 것으로 나타났다. BPA로 유도된 3T3-L1 전구지방세포에서 XTT assay 결과 sinigrin 180 µM 및 갓 추출물 300 ㎍/mL 농도에서 세포 독성을 보이지 않았으며, 지방세포 분화과정 중 세포 내 지방 축적량과 ROS 생성량을 비교하였을 때 갓과 sinigrin을 처리한 지방세포의 경우 지방축적량 및 ROS 생성량 모두 유의적으로 감소시키는 것으로 나타났다. 또한, 갓 추출물 및 sinigrin을 처리하였을 때 지방세포 분화를 조절하는 전사인자 PPARγ, C/EBPα 및 aP2의 발현이 억제됨을 확인하였다. 이 결과를 통해 갓은 환경호르몬 비스페놀 A로 유도된 지방세포 내 지방 축적 억제와 더불어 ROS 저감에 효과적으로 작용함을 확인하였다. 향후 sinigrin을 함유한 갓은 BPA로 인한 지질 대사 장애를 예방하는 천연물 유래 기능성 식품 소재로 활용할 가능성이 높은 것으로 기대되며, 추가로 임상 연구 및 작용기전 입증을 위한 in vivo 모델에서의 후속 연구가 진행되어야 할 것으로 사료된다.